1855 Ill. Criminal Code 365, Offenses Against the Persons of Individuals, Div. V, § 43 - (:unkn) unknown (General Publisher, 1855)
Prohibited dueling or agreeing to duel or single combat with any engine, instrument, or weapon where the probably consequence might be the death of either party, and shall kill his antagonist, or shall inflict a wound where the party shall die within one year. Each violator, his second, the second of the person killed, all aiders, abettors, and counselors convicted shall be punished under a high misdemeanor, punished by a prison term not less than one nor more than five years.
--
Keywords: DUELING